IMPORTANCE OF TEACHING STRATEGIES FOR A2 ENGLISH LANGUAGE LEARNERS IN INCLUSIVE CLASSROOMS: IMPORTANCE OF TEACHING STRATEGIES FOR A2 ENGLISH LANGUAGE LEARNERS IN INCLUSIVE CLASSROOMS - Azatbavea, Miyasar (Журнал иностранных языков и лингвистики, 2025)
The A2 level in the Common European Framework of Reference for Languages (CEFR) represents a crucial stage for English language learners. At this level, students are expected to understand and use basic everyday expressions and simple sentences (Council of Europe, 2001).[1,4] Vocabulary acquisition is paramount at this stage, as it forms the bedrock for further language development and communicative competence. However, the challenges are magnified when these learners are integrated into inclusive educational classrooms, which cater to a wide spectrum of abilities and learning needs. Learnerscan easily and naturally do this in their own language and they cannot do this in foreign language[5]. Inclusive settings require educators to implement differentiated strategies that address the diverse learning profiles of all students. This article aims to identify and explore research-backed, practical pedagogical approaches for vocabulary instruction that can effectively support A2 level ELLs within these inclusive environments.